Knowledge, Attitudes, and Practices Associated with the Selection of Sweetened Ultra-Processed Foods and Their Importance in Oral Health - María del Pilar Angarita-Díaz; Johao Alexander Colmenares-Pedraza; Valentina Agudelo-Sanchez; Juliana Alejandra Mora-Quila; Laura Sofia Rincón-Mejia (MDPI AG, 2024)
Background: Reading nutritional labelling helps consumers select healthier food, thereby benefitting their oral health. The purpose of this study was to describe the knowledge, attitudes, and practices (KAPs) of parents and carers of children and preteens, associated with reading nutritional labelling, selecting sweetened ultra-processed foods, and their impact on oral health. Materials and Methods: This was a descriptive cross-sectional study in which a validated questionnaire was administered to 298 parents and caregivers of children aged 1-12 years from different districts in Villavicencio, Colombia. Participants' scores, based on the number of correct answers, were used to classify their level of KAP as low, medium, or high. In addition, the frequency of responses, the KAP levels, and the median scores were analysed. Finally, associations were determined using the chi-square test. Results: Most participants reached a medium level in terms of knowledge (41.6%) and attitudes (49.3%) and a low level in terms of practices (43.3%). An association was found between participants' level of KAPs and their socioeconomic and educational level (p < 0.05). Conclusions: The study findings reveal inadequate KAPs associated with nutritional labelling, adequate food selection, and the importance of oral health.